Trade and the Spatial Distribution of Transport Infrastructure - Alexander Tarasov; Gabriel Felbermayr (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper endogenizes the spatial distribution of infrastructure investment and transportation costs. Transportation costs between two addresses depend on cumulative infrastructure investment. In a continuous space setting with several independent countries or regions, consumers demand domestic and foreign goods, while central planners care only about welfare of their own constituencies. The equilibrium of the game between countries features under-investment and excessive spatial variation. The distribution of infrastructure is skewed towards central regions, rationalizing the non-linear trade-impeding role of distance in empirical gravity models and the so called border puzzle. We find that the endogenous allocation of infrastructure investment magnifies small discrete border frictions and creates `border regions' within countries. Privatizing infrastructure provision does not solve the problem. French data on transportation costs and an empirical gravity model for trade between US states motivate and corroborate our theory.
Keywords: F11; R42; R13; 330